2002
DOI: 10.1016/s1074-7613(02)00361-8
|View full text |Cite
|
Sign up to set email alerts
|

Rare, Structurally Homologous Self-Peptides Promote Thymocyte Positive Selection

Abstract: Although it is clear that positive selection of T cells involves recognition of specific self-peptide/MHC complexes, the nature of these self-ligands and their relationship to the cognate antigen are controversial. Here we used two complementary strategies to identify naturally occurring self-peptides able to induce positive selection of T cells bearing a specific T cell receptor, OT-I. Both the bioassay- and bioinformatics-based strategies identified the same self-peptides, derived from F-actin capping protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 54 publications
5
113
0
Order By: Relevance
“…MHC-bound self-peptides influence development of immature thymocytes (42,43), and mature T cells interact with Ags from foreign pathogens presented by self-MHC or self-peptides presented by foreign MHC molecules. The alloreactive T cells can originate from both naive and memory T cell populations (44).…”
Section: Discussionmentioning
confidence: 99%
“…MHC-bound self-peptides influence development of immature thymocytes (42,43), and mature T cells interact with Ags from foreign pathogens presented by self-MHC or self-peptides presented by foreign MHC molecules. The alloreactive T cells can originate from both naive and memory T cell populations (44).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that only those cells that express TCRs with the appropriate specificities are allowed to mature, DP thymocytes are subjected to a selection process on the basis of their TCR specificity for peptideþMHC that promotes the survival and differentiation of functionally competent cells ( positive selection) and triggers the deletion of overtly autoreactive cells (negative selection) (Sebzda et al 1999;Starr et al 2003). Positive selection is thought to be mediated by relatively weak non-agonist peptides (Hogquist et al 1994;Santori et al 2002) indicating that amplification of TCR signals generated from such interactions may be especially important for positive selection. Consistent with this notion, positive selection was found to be markedly impaired in zdeficient mice reconstituted with transgenes encoding ITAM mutant z chains (Shores et al 1994;Ardouin et al 1999;Pitcher et al 2005b).…”
Section: Potential Functions For Itam-mediated Signal Amplification Dmentioning
confidence: 99%
“…However, none of these studies provides evidence that the respective peptides actually contribute to negative selection under physiological conditions. In the early nineties, Marrack et al 17 successfully identified B20 MHC IIbound peptides in pooled thymi of several hundred mice and a few natural ligands for positive selection of mouse OT-I cells are known 18,19 . More recently, another group has eluted peptides from whole-mouse thymus, using bioinformatics to narrow down on likely MHC I ligands 20 .…”
mentioning
confidence: 99%